The 3 July Affair, 1946: Opposition Movement Against Syahrir's Cabinet - Syafruddin Yusuf (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2024)
Abstract: The events of July 3 1946 are a portrait of hard-line national leaders who did not agree with the diplomatic politics of the Syahrir government. They want to replace Syahrir's cabinet with a new cabinet that they have prepared. This research aims to determine the background to the 3 July 1946 incident, the process of the 3 July 1946 incident, and the resolution of the 3 July incident. The method used in this research is the historical method with heuristic stages, source criticism, interpretation and historiography. Based on research results, it is known that the 3 July incident started with the kidnapping of Syahrir and developed into a movement that culminated in a government coup by forcing Soekarno to sign a decree to replace the government. The Syahrir opposition group's efforts failed because Soekarno refused to sign the decree. They were later arrested, tried and sentenced. President Soekarno's attitude in rejecting the opposition's desire to replace Syahrir's government shows that Syahrir received strong support from Soekarno. Soekarno's attitude shows that Sukarno was a strong and firm Republican leader who was appreciated or respected by other Indonesian leaders. Abstrak: Peristiwa 3 Juli 1946 merupakan potret pemimpin nasional garis keras yang tidak setuju dengan politik diplomasi pemerintahan Syahrir. Mereka ingin mengganti kabinet Syahrir dengan kabinet baru yang sudah mereka siapkan. Penelitian ini bertujuan untuk mengetahui latar belakang terjadi peristiwa 3 Juli 1946, proses terjadinya peristiwa 3 Juli 1946, dan penyelesaian peristiwa 3 Juli tersebut. Metode yang digunakan dalam penelitian ini adalah metode sejarah dengan tahapan heuristik, kritik sumber, interpretasi dan historiografi. Berdasarkan hasil peneitian diketahui bahwa Peristiwa 3 Juli bermula dari penculikan Syahrir dan berkembang menjadi gerakan yang berujung pada kudeta pemerintahan dengan memaksa Soekarno menandatangani dekrit pengganti pemerintahan. Upaya kelompok oposisi Syahrir gagal karena Soekarno menolak menandatangani dekrit tersebut. Mereka kemudian ditangkap, diadili dan dijatuhi hukuman. Sikap Presiden Soekarno yang menolak keinginan pihak oposisi untuk menggantikan pemerintahan Syahrir menunjukkan bahwa Syahrir mendapat dukungan kuat dari Soekarno. Sikap Soekarno tersebut menunjukkan bahwa Sukarno adalah pemimpin Republik yang kuat dan tegas sehingga dihargai atau dihormati oleh para pemimpin Indonesia lainnya.